THE SAFETY OF EXCIPIENTS AS A KEY FACTOR IN SUCCESSFUL DRUG DEVELOPMENT - DEMINA, NATALIA; BAKHRUSHINA, ELENA; ANUROVA, MARIA; ABUELEZ, SALMA; ZUBAREVA, IRINA; KRASNYK, IVAN (International Journal of Applied Pharmaceutics, 2025)
Until recently, the safety of excipients had not received much attention, as they were considered pharmacologically indifferent and were included in medicinal products solely to facilitate production or to enhance ease of use. In recent years, excipients have come under greater scrutiny regarding their potential adverse effects on the body, which may have implications for patient safety during routine and long-term use. This article addresses certain aspects of the regulatory framework for excipients in the United States as well as in the countries of the European and Eurasian Unions. Various sources of information on the physicochemical and biological properties of pharmaceutical excipients are examined, along with examples of adverse effects associated with several widely used excipients. Descriptions of electronic databases containing information on excipients in the context of their application are provided, considering dosage, route of administration, dosage forms, and potential biological targets. A comparison of these databases is also provided.